Enabling a new degree of wave control with metamaterials: a personal perspective. (21st July 2017) - Alù, Andrea; Engheta, Nader
Abstract: Metamaterials represent an exciting area of research, which has rapidly evolved in the past two decades from basic research to applied technology, and it now encompasses a broad range of scientific communities, with continuous and exciting scientific progress. Our personal journey in the field of artificial materials and metamaterials spans over many years, and has brought us through an exciting adventure in the theoretical understanding of wave interactions with materials, with several implications for new devices and components for radio-wave, infrared, optical and acoustic technology. In this paper, we provide a brief overview of some highlights of our contribution to this area of research, looking forward to several exciting opportunities for further scientific and technical progress in this area of science and technology.